I have been on it for few days now, maybe someone could tell me I am on the right track.
So i got 2 points of a linear graph:
Ax, Ay Bx, By
Also I got a statement :
foo = (Cx - Bx) / (Cy - By)
I need to find Cx, Cy
Now I have been trying to do it using linear graph equation. (y = mx + b)
Ax, Ay, Bx, By, I get
b for the linear graph.
Ending up with:
foo = (Cx - Bx) / ( (m * Cx + b) - By)
Cx, i get :
Cx = (foo * (By - b) - Bx) / (foo * s - 1)
I have been reworking this one for a while now, but the results are not as expected.
--== START of EDIT ==--
Cx equation I got above, I get
Cx = Bx, or very close to it. (I run it on Python)
foo > Cx > Bx
--== END if EDIT ==--
I wonder if this is a correct way of doing it and if I made some mistake. If so - maybe someone could point it out for me :)